HRO and RE: A pragmatic perspective. (August 2019) - Haavik, Torgeir K.; Antonsen, Stian; Rosness, Ragnar; Hale, Andrew
Highlights: We use a pragmatic approach to discuss the relationship between HRO and RE. HRO and RE are different with regard to symmetry, normativity, addressee and origin. We recommend more exploitation of controversies to produce fertile discourses. We argue against fusing HRO and RE into a "theory of everything". Future empirical research should explore the borderlands between HRO and RE. Abstract: This special issue invites to a debate to elaborate on differences and similarities between the perspectives of High Reliability Organisation (HRO) and Resilience Engineering (RE). Such a debate may be conducted along both essentialistic and pragmatic lines, and we suggest that the latter approach is potentially more interesting and fruitful than the first. We use the technique of feeding off controversies and expand on what might at first look merely like a polemic disagreement, a question of wording, namely the definition of safety as a dynamic non-event. This elaboration is used as a projector onto a canvas where a number of distinguishing themes between HRO and RE are outlined more clearly; symmetry, normativity, addressee and origin are keywords that show how HRO and RE are different, and why they cannot simply be combined into one grand theory of everything. Other concrete results from these investigations include a review of applications of HRO and RE in health research, an elaboration of the distinction between Safety I and Safety II, and a nuancing of how we may understand and study successful operations. We suggest a research agenda that combines the scopes and methods of HRO and RE, possibly in combination with other theoretical approaches. We also call for a more lively discussion on central themes of HRO and RE, not for fighting over definitions and proving who is right, but with the aim of producing knowledge that makes a difference regardless of theoretical stance.